2009
DOI: 10.1189/jlb.0209053
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil antimicrobial defense against Staphylococcus aureus is mediated by phagolysosomal but not extracellular trap-associated cathelicidin

Abstract: Neutrophils kill invading pathogens by AMPs, including cathelicidins, ROS, and NETs. The human pathogen Staphylococcus aureus exhibits enhanced resistance to neutrophil AMPs, including the murine cathelicidin CRAMP, in part, as a result of alanylation of teichoic acids by the dlt operon. In this study, we took advantage of the hypersusceptible phenotype of S. aureus DeltadltA against cationic AMPs to study the impact of the murine cathelicidin CRAMP on staphylococcal killing and to identify its key site of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 53 publications
1
59
1
Order By: Relevance
“…Some bacteria, such as Mycobacterium tuberculosis, cannot be killed by NETs (44), but a variety of other pathogens are very sensitive to killing by high local concentrations of antimicrobial components such as proteases and histones from NETs (9,26,52). In addition to elastase, MPO, and defensins, other mediators recently implicated in netosis include the LL-37 cathelicidin against S. flexneri (23) and Staphylococcus aureus (33) and calprotectin against Candida albicans (52). Nucleus-derived histones also play a role in pathogen killing by NETs, notably, during Leishmania amazonensis infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…Some bacteria, such as Mycobacterium tuberculosis, cannot be killed by NETs (44), but a variety of other pathogens are very sensitive to killing by high local concentrations of antimicrobial components such as proteases and histones from NETs (9,26,52). In addition to elastase, MPO, and defensins, other mediators recently implicated in netosis include the LL-37 cathelicidin against S. flexneri (23) and Staphylococcus aureus (33) and calprotectin against Candida albicans (52). Nucleus-derived histones also play a role in pathogen killing by NETs, notably, during Leishmania amazonensis infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…46 Previous studies have shown that latex beads and antimicrobial peptides target the macrophage phagosomes, resulting in increased maturation of phagosomes 46 and intracellular killing of S. aureus, 47 respectively. The authors also observed active uptake of PI-labeled CS-AgNPs by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…No increase was observed in the tumor-bearing mice treated with vehicle or in the tumor-free mice treated with LPS, suggesting a stronger effect of LPS on chromatin release in the tumor-bearing mice. To assess whether DNA originated from NETs, we evaluated the presence of cathelicidin-related antimicrobial peptide (CRAMP), the murine homolog of human cathelicidin, a protein highly expressed in neutrophils and shown to be associated with NETs (29), and H3Cit in the plasma. Whereas a small increase in CRAMP was observed in the plasma of LPS-treated tumor-free mice, a higher level was observed in the plasma of LPS-treated tumor-bearing mice (Fig.…”
Section: Spontaneous Net Formation In Cancer Is Associated With the Pmentioning
confidence: 99%